Evaluation of pesticides against rice sheath blight caused by Rhizoctonia solani - P. SHARMA and R.T.P. PANDIAN, G. PRAKASH*, U.D. SINGH, (Indian Phytopathology, 2013)
Sheath blight is one of the most widespread diseases of rice caused by Rhizoctonia solani. In this study, In vitro evaluation of 30 commonly used pesticides (10 fungicides, 10 insecticides and 10 herbicides), has been taken into account to study the effect of single or combined pesticide action on the mycelial growth, sclerotial formation and germination in R. solani and their compatibility. Observations as recorded revealed that, effect of fungicides like carbendazim and hexaconazole showed high efficacy on mycelial growth inhibition, sclerotial formation and sclerotial germination compared to other fungicides in its individual testing under in-vitro condition. In the case of insecticides, 0% to 31.08% growth inhibition was recorded at all the three concentrations of endosulfan and chlorpyriphos which inhibited the mycelial growth in the range of 0% to 16.86%. Among herbicides, thiobencarb inhibited the mycelial growth in the range of 0% to 26.45% at all the three concentrations and butachlor showed growth inhibition of 0% to 15.70%. Insecticides and herbicides had no effect on sclerotial formation and germination of sclerotia at all the three concentrations. Among the compatibility study with different pesticides, fungicides like carbendazim and hexaconazole with insecticides (endosulfan, chlorpyriphos) and herbicides (thiobencarb, butachlor) showed better results in the range of 86.40% to 100% and 72.09% to 100% respectively at all the three concentrations against R. solani. Thus, it helps to evolve a economically cheaper and environment friendly methodology that may be useful for the farming community to overcome the detrimental effect of Rhizoctonia solani.